2008
DOI: 10.1007/s11010-008-9849-7
|View full text |Cite
|
Sign up to set email alerts
|

Identification, purification, and characterization of a secretory serine protease in an Indian strain of Leishmania donovani

Abstract: An aprotinin sensitive serine protease was identified in the culture supernatant of the Indian strain of Leishmania donovani (MHOM/IN/1983/AG83). The protease was subsequently purified and characterized. The apparent molecular mass of the enzyme was 115 kDa in SDS-PAGE under non-reducing condition, while on reduction it showed a 56 kDa protein band indicating that the protease is a dimeric protein. The purified enzyme was optimally active at the pH and temperature of 7.5 and 28 degrees C, respectively. Assays … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…Our previous study demonstrated that a 115-kDa serine protease is secreted by an Indian strain of L. donovani (8). In the present report, we have demonstrated the intracellular localization of this parasite-derived secreted serine protease and also its differential expression in virulent, avirulent, and attenuated strains of L. donovani as well as in different cell cycle stages of the parasite.…”
supporting
confidence: 66%
See 1 more Smart Citation
“…Our previous study demonstrated that a 115-kDa serine protease is secreted by an Indian strain of L. donovani (8). In the present report, we have demonstrated the intracellular localization of this parasite-derived secreted serine protease and also its differential expression in virulent, avirulent, and attenuated strains of L. donovani as well as in different cell cycle stages of the parasite.…”
supporting
confidence: 66%
“…The migration of the parasite in host tissues is mediated by the release of proteolytic enzymes that can degrade the tissue barriers. Potent proteolytic enzymes of cysteine, serine, and metalloprotease classes have been identified in secretory products of many of the parasites (8,19,26,27,30). Serine proteases have been reported to have strong hydrolytic activity against a wide range of extracellular matrix (ECM) components and human plasma proteins; hence, they are thought to play vital roles in the host tissue invasion process (17).…”
mentioning
confidence: 99%
“…A similar serine protease was found in the supernatant culture of L. donovani with the same molecular weight of 115 KDa [27] and with the same localization, mainly in flagelar pockets by immunohistochemistry [28]. The expression of the protease was correlated to a high virulence for the parasite and to the metacyclic stage of L. donovani promastigotes [28].…”
Section: Secreted Serine Protease (Psp) From L Donovanimentioning
confidence: 60%
“…A released enzyme of 110 kDa was also identified and seems to occur as a homodimer [187]. Similar enzymes were also identified in L. braziliensis [188] and L. donovani [189]. A common feature of these enzymes seems to be their ability to digest a wide range of proteinaceous substrates and several enzymes are homodimeric or heterodimeric proteins.…”
Section: Serine Peptidasesmentioning
confidence: 61%